Decision Support System for Controlling the Establishment Permit of Raudhatul Athfal (RA) Using the Multi Attribute Utility Theory Method - Santoso, Heri; Suendri, S; Afandi, Ade Aminah (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2023)
At the Labuhanbatu Selatan Ministry of Religion office, there were problems in selecting the Raudhatul Athfal (RA) establishment permit registration file, because the admin was still selecting files one by one without using accurate calculations, so the process of obtaining a recommendation for Raudhatul Athfal (RA) establishment permit took a long time. . Therefore we need a Decision Support System (DSS) to help simplify the decision-making process by using the Multi Attribute Utility Theory (MAUT) method which will weight each criterion where the highest criterion weight value influences the interests of the other criteria so as to produce calculations with high accuracy values. Calculations are carried out by manual calculations or system calculations. The application for selecting the Raudhatul Athfal (RA) establishment permit file is a web-based application where the application will perform calculations and perform rankings quickly and accurately in determining which madrasas will later receive a recommendation for Raudhatul Athfal's establishment permit.